Pemetaan Tingkat Rawan Bencana Banjir di Daerah Aliran Sungai Maros Provinsi Sulawesi Selatan - Badwi, Nasiah; Invanni, Ichsan; Abbas, Ibrahim (UNIVERSITAS NEGERI MAKASSAR, 2020)
Indonesia is an archipelago with a tropical climate with very high rainfall. In the rainy season floods occur which cause losses, namely loss of life and property. This condition is a routine disaster that always threatens people's lives. Therefore, research needs to be done to identify flood-prone areas and flood-causing factors in the Maros River Basin. The method used to determine flood-prone areas is used by a combination of remote sensing, terrestrial, secondary data and interviews using the criteria of Sutikno et al (1995) with development. The variables used topography (flat and sloping), soil texture, drainage, inundation time and flood return period. The analysis shows that in the Maros watershed there are 3 classes that are prone to flooding namely not prone, prone and very prone. Most are vulnerable because more than 50 percent of the area is at a vulnerable and very vulnerable level. The class is very prone to spread from downstream to the middle of the watershed, covering the southern sub-districts of Maros Baru, Marusu, Turikale, southern Bantimurung, western Simbang, northern Mandai and northern Tanralili. The contributing factors are high rainfall, flat and sloping topography, fine soil texture in the downstream river, poor drainage due to poor waste management, land use dominated by ponds and paddy fields and high flood return periods.